Information Interaction between LIMSand Corporate Information SystemElements at Enterprise - Safianov A. S. Aleksander Sergeevich; Tereshchenko A. G. Anatoly Georgievich; Tereshchenko V. A. Vasily Anatolievich; Yanin A. M. Anton Mikhailovich; Yunak A. L. Alexander Lvovich; Tereshchenko O. V. Olga Vasilievna (2012, 2012)
Title screen